ANALYSIS OF THE QUALITY OF PUBLIC SERVICES FOR MAKING FAMILY CARDS (KK) AT THE POPULATION AND CIVIL REGISTRATION OFFICE (DISDUKCAPIL) OF GAYO LUES REGENCY - Furqan Lutfi; Adam Adam; Maksum Syahri Lubis (SOSIOEDUKASI, 2025)
This study analyzes the quality of Family Card (KK) issuance services at the Population and Civil Registration Office (Disdukcapil) of Gayo Lues Regency. Using a qualitative method with a descriptive approach, this study identifies the primary obstacles to services, including network disruptions, power outages, limited service personnel, and a lack of supporting facilities. Although the KK issuance procedure is promised to be completed within one working day, various external and internal factors cause service delays. Based on Zeithaml's theory of service quality, it was found that aspects of reliability, physical evidence, and Responsiveness still require improvement. To overcome these obstacles, Disdukcapil needs to improve its technological infrastructure, increase the number of service personnel, and provide better supporting facilities for the community. Periodic training for officers is also required to enhance professionalism and Responsiveness in delivering services. In addition, collaboration with the central government in strengthening the population administration system is a strategic step to ensure more effective, transparent, and accountable services. This research is expected to serve as a reference for efforts to improve public services in the field of population administration.